UJI TEPUNG BIJI MENGKUDU (Morinda citrifolia L.) TERHADAP HAMA BUBUK JAGUNG Sitophilus zeamais M. (Coleoptera; Curculionidae) - Rusli Rustam; Maya Audina (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2018)
Sitophilus zeamais M. was a warehouse pest that attacks corn kernels in storage. S. zeamais pest control commonly used fumigant insecticides that used still has many disadvantages such as food safety impacts, environmental pollution and pest resistance, so that a safe alternative to control was needed, one of which was using noni seeds. This research was aimed to obtain a dose of noni seed flour that was effective to S. zea mays corn powder pest mortality.The research was conducted at the Laboratory of Plant Pest, Faculty of Agriculture, University of Riau from March to May 2018.The treatment used was the dose of noni seed flour 0 g.100 g-1 corn, 2 g.100 g-1 corn, 4 g.100 g-1 corn, 6 g.100 g-1 corn, and 8 g.100 g-1 corn. This research was conducted experimentally using a completely randomized design (CRD) with 5 treatments and 4 replications. Based on the results of the research, the dose of noni seeds 8 g.100 g-1corn had not been effective in controlling S. zeamais with mortality of 52.50%, shrinkage of corn seed weight by 8.78% and an increase in individuals by 8.20.Keywords: Morinda citrifolia L., Sitophilus zeamais M., Zea mays